2017
DOI: 10.1016/j.joco.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bandage contact lens removal on the fourth versus seventh postoperative day after photorefractive keratectomy: A randomized clinical trial

Abstract: PurposeTo compare the outcomes of bandage contact lens (BCL) removal on the fourth versus seventh post-operative day following photorefractive keratectomy (PRK).MethodsThis study recruited eyes of patients who underwent PRK surgery. The patients were randomly assigned to 2 groups. In Group 1 BCL was removed on the 4th postoperative day, while in Group 2, BCL was removed on the 7th postoperative day. After BCL removal, patients were asked to express their pain score and eye discomfort. At one and three months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Bandage contact lenses are soft lenses that are placed in the patient's eye for night and day use until removed by the practitioner. They are frequently used in ophthalmic corneal surgery under the premise that they enhance patient comfort and healing 59 . Our literature search identified only a limited number of studies evaluating this treatment in patients with traumatic corneal abrasions and as such there is insufficient evidence to support or refute benefits to healing or pain control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandage contact lenses are soft lenses that are placed in the patient's eye for night and day use until removed by the practitioner. They are frequently used in ophthalmic corneal surgery under the premise that they enhance patient comfort and healing 59 . Our literature search identified only a limited number of studies evaluating this treatment in patients with traumatic corneal abrasions and as such there is insufficient evidence to support or refute benefits to healing or pain control.…”
Section: Discussionmentioning
confidence: 99%
“…They are frequently used in ophthalmic corneal surgery under the premise that they enhance patient comfort and healing. 59 Our literature search identified only a limited number of studies evaluating this treatment in patients with traumatic corneal abrasions and as such there is insufficient evidence to support or refute benefits to healing or pain control. While the included studies found no complications, infectious keratitis was reported in two prior case series in the treatment of corneal abrasions.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of BCL on the seventh postoperative day had lower pain scores compared with the removal on the fourth postoperative day (P¼0.07). 46 Considerable reduction in pain was observed on the third postoperative day compared with the first postoperative day, with the pain tapering off from the fourth day with lotrafilcon B, comfilcon A, lotrafilcon A, balafilcon A, and senofilcon A eyes. 9,19,34,[37][38][39][40] Lesser pain was observed with senofilcon A on the first postoperative day compared with other BCLs.…”
Section: Photorefractive Keratectomymentioning
confidence: 94%
“…9 Uncorrected visual acuity (UCVA) was improved considerably on the seventh postoperative day with BCL application. 43 The removal of BCL on the seventh postoperative day was beneficial compared with that on the fourth postoperative day 46 in visual rehabilitation (corrected distance visual acuity and uncorrected distance visual acuity; P¼0.016) after 1 month. A similar study showed that the removal of BCL on the third or fifth postoperative day yielded no significant benefits in visual acuity.…”
Section: Photorefractive Keratectomymentioning
confidence: 99%
“…To further investigate the parameters associated with BSCL wear and pain control, a prospective study examined the timing of BSCL removal in 260 eyes of 130 patients, removing the lens either on day 4 or day 7 post-operatively [105]. They found no differences in pain between the two groups, although interestingly, the group in which the BSCL was removed on day 4 post-op had an increase in the frequency of complications, including filamentary keratitis, corneal erosion, and haze.…”
Section: Photorefractive Keratectomy (Prk)mentioning
confidence: 99%